Hydrogeochemical characteristics of the Ozancik hot spring, Canakkale, Turkey - Pehlivan, Rustem (Journal of Nepal Geological Society, 2001)
This investigation was carried out to determine the hydrogeochemical characteristics of the Ozancik hot spring. The study area is located about 15 km southwest of the town of Can, Canakkale. During the investigation, a geological map of the hot spring and its surroundings was prepared, and hot water and rock samples were collected from the study site. The Palaeogene-Neogene andesite, trachyandesite, andesitic tuff, silicified tuff, and tuffites form the basement rocks and they are overlain by the Quaternary alluvial deposits. The chemical analysis of hot water indicates that it is rich in SO42-(575 ppm), Cl-(193.2 ppm), HCO3-(98.5 ppm), Na+(315 ppm), K+(7.248 ppm). Ca2+(103 ppm), Mg2+(0.274 ppm), and SiO2(43.20). The distribution of ions in the hot water on the Schoeller diagram has an arrangement of r(Na++K+)>rCa2+>rMg2+and r(SO42-)>rCl->r(HCO3-). In addition, the inclusion of Fe2+, Cu2+, Cr3+, Mn2+, Ni2+ and Hg2+ in the hot water samples indicates potential natural inorganic contamination. The water analysis carried out following the ICPMS-200 technique was evaluated according to the World Health Organization and Turkish Standards. The utilisation and the effects of the hot water on human health are also discussed in the paper.